2012
DOI: 10.4028/www.scientific.net/amr.500.128
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Intermittent Turning 2.25Cr-1Mo-0.25V Steel with Coated Cemented Carbide Tool

Abstract: In order to improve the machining efficiency and tool life in manufacturing process of hydrogenation reactor shell components, the cutting performance of quadrate GC4235 coated carbide tool in intermittent turning 2.25Cr-1Mo-0.25V steel was investigated, the optimal cutting parameters were obtained. The empirical mathematical models of relationships among the amount of metal removal, tool life, cutting force and cutting parameters were established. The failure mechanism of the GC4235 carbide coated tools for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Each of the four input parameters (Vc, r, ap, and f) was varied thrice (Table 3), enabling us to construct the experimental matrix for the Taguchi L9 design (Table 4). All selected operational conditions for conducting the experiments are organized in Table (5).…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the four input parameters (Vc, r, ap, and f) was varied thrice (Table 3), enabling us to construct the experimental matrix for the Taguchi L9 design (Table 4). All selected operational conditions for conducting the experiments are organized in Table (5).…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…In another similar study, H.L. Liu et al [5] presented empirical models of parameters (MRR) and (Fz) in relation to factors (Vc), (ap), and (f) after conducting experiments in (IT) of 2.25Cr-1Mo-0.25V material using (GC4235) cutting tool. They found that the primary wear mechanisms at low cutting speeds are abrasive wear and chipping, whereas coating delamination and adhesive wear are predominant in high cutting speed cases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study revealed that the performance of the tool (GC4235) is superior to that of the tool (YT5). The cutting performance of a quadrate (GC4235) coated carbide tool in IT of 2.25Cr1Mo0.25V material was investigated by Liu et al [5]. There have been proposed empirical models of the parameters (MRR) and (Fz) as a function of the factors (Vc), (ap), and (f).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the tool performance GC4235 is superior to the tool YT5. Liu et al [7] conducted experiments in IT on 2.25Cr-1Mo-0.25V material with a coated carbide tool GC4235. Empirical models of MRR and Fz parameters as a function of Vc, ap, and f were proposed.…”
Section: Introductionmentioning
confidence: 99%